A histological study of human derived tooth-hydroxyapatite (THA) - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
Different types of bone-graft substitutes have been developed and are in the market worldwide to eliminate the drawbacks of autogenous grafting. They vary in composition, strength, osteoinductive and osteoconductive properties, mechanism and rates by which they are resorbed and remodelled. Tooth derived hydroxyapatite (THA) is a novel biomaterial. This study was performed to determine the histological properties of THA on animals. A commercial coralline HA (CHA, Proosteon 200, Interpore Cross, USA) was used as control material. 20 sheeps were used and divided into 2 groups. Human THA (Group A) and CHA (Group B) materials were implanted to the tibiae of 10 sheeps for each group. The histological examinations of surrounding bone response were done 12 weeks after implantation. There was no significant difference histologically between group A and B. All materials were found to be surrounded by new bone tissue. THA was found to be as efficient as the standard CHA on histological basis. In addition, economical production of THA should be taken into consideration. Therefore, THA may be a viable alternative on bone grafting provided that clinical trials will be completed.
Keywords: hydroxyapatite; grafting; bone graft; osteoconduction; BOVINE CANCELLOUS BONE; BIOMEDICAL APPLICATIONS; YIELD MATERIALS